Integrated photocatalysis adsorption processes for oxytetracycline removal: Using volborthite and its composite with g-C3N4 - Wee, Weiqing; Sim, Lan Ching; Leong, Kah Hon; Azrina, Abd Aziz (Springer, 2024)
The photocatalytic-adsorption performance of the composites of volborthite (CuVA) and graphitic carbon nitride (g-C3N4) was studied in this work using oxytetracycline (OTC) as model pollutant under LED light irradiation. CuVA at different weight percentages (10, 30, 50), namely, C10, C30, and C50, were loaded onto graphitic carbon nitride using wet chemical method. The physical, chemical, and optical properties were evaluated via various analytical techniques. Through integrated adsorption-photocatalytic process, no significant photocatalytic reaction occurred in g-C3N4 and the composite even after 4 h of irradiation. The setup was modified such that each run was conducted in the presence and absence of light. Aside from photolysis and g-C3N4, all composites performed better under the presence of light in which CuVA improved the most from ~ 50% down to ~ 20% of initial concentration. CuVA performed almost identically (80% removal of OTC) under the presence of light irradiation at ambient temperature (22 °C) and in the dark at 32 °C, confirming that temperature was the contributing factor to the improvement instead of light. CuVA exhibited excellent adsorption capacity of 171 mg/g and adsorption rate of 90% towards the removal of highly concentrated OTC (100 mg/L) under optimized parameters of pH 5.0 and at 42 °C after 3 h of adsorption process. Life cycle assessment revealed that close to 50% of fresh 100 ppm OTC could be removed after five cycles without any desorption process.